Identifikasi Faktor Kesulitan Belajar Membaca Siswa di Kelas VI di SDN Karangpawitan III - Apriandini, Iyar; Novani, Deva; Amelia, Amelia; Sari, Sonia Nadia; Alpian, Yayan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the factors that cause difficulties in learning to read for students. The type of this research is descriptive qualitative research. The subjects of this research consist of sixth grade students and the homeroom teacher of the sixth grade. Data collection methods include interviews, observations, and documentation. The data obtained is then analyzed to determine the internal and external factors that cause difficulties in learning to read for students. The results of the study show that the factors causing difficulties in learning to read for sixth grade students at SDN Karangpawitan III are caused by internal factors (low intelligence, low student learning motivation, low student interest in reading, as well as social and emotional maturity and unstable student adjustment) and external factors (less varied teaching methods by teachers and lack of parental attention to students in the family environment). Therefore, it can be concluded that there are several factors causing difficulties in learning to read for students, namely internal and external factors.